The social cost of carbon dioxide under climate-economy feedbacks and temperature variability. (6th September 2021) - Kikstra, Jarmo S; Waidelich, Paul; Rising, James; Yumashev, Dmitry; Hope, Chris; Brierley, Chris M
Abstract: A key statistic describing climate change impacts is the 'social cost of carbon dioxide' (SCCO2 ), the projected cost to society of releasing an additional tonne of CO2 . Cost-benefit integrated assessment models that estimate the SCCO2 lack robust representations of climate feedbacks, economy feedbacks, and climate extremes. We compare the PAGE-ICE model with the decade older PAGE09 and find that PAGE-ICE yields SCCO2 values about two times higher, because of its climate and economic updates. Climate feedbacks only account for a relatively minor increase compared to other updates. Extending PAGE-ICE with economy feedbacks demonstrates a manifold increase in the SCCO2 resulting from an empirically derived estimate of partially persistent economic damages. Both the economy feedbacks and other increases since PAGE09 are almost entirely due to higher damages in the Global South. Including an estimate of interannual temperature variability increases the width of the SCCO2 distribution, with particularly strong effects in the tails and a slight increase in the mean SCCO2 . Our results highlight the large impacts of climate change if future adaptation does not exceed historical trends. Robust quantification of climate-economy feedbacks and climate extremes are demonstrated to be essential for estimating the SCCO2 and its uncertainty.